Pendampingan Budidaya Maggot Sebagai Strategi Pengolahan Sampah Bernilai Ekonomi di Desa Jagaita, Kabupaten Bogor - Primadhita, Yuridistya; Jayadi, Jayadi; Susanti, Juliya; Mardhiyah, Rifdah; Fajri, Alfidha Sepyantini; Herlina, Elin; Marshela, Prolice Anggraeni (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to assist in waste processing that can have economic value for the community. This activity is in collaboration with Karang Taruna Jagaita Village and community representatives from June 2 to July 28, 2023. The activity began with socialization regarding the importance of waste management, knowing the potential of waste that can have economic value, knowing the negative effects of waste, sorting and separating waste into categories that can be recycled and those that cannot be recycled. Furthermore, waste processing is carried out which is ready to be used for BSF maggot breeding. The results of the mentoring activity are that the community understands how to process organic waste and maggot breeding and also obtains economic benefits.